Pengembangan Modul Berbasis Multiple Intelligence Pada Materi Sistem Pencernaan untuk siswa SMP kelas VIII - NISA, KHOIRUN; IZA, NIKMATUL (Universitas Insan Budi Utomo, 2024)
Learning is a reciprocal interaction relationship between learning participants and teachers. Learning carried out by playing is as high quality and effective as possible. Learning can be said to be effective if all components involved in learning can support each other, so that children will gain an understanding of what they are learningThis. Research activities are integrated throughout the product development process. This development research model uses the R & D research model, namely through 1). Research and data collection, 2) planning, 3) development of initial product draft, 4) initial field trials, 5) revision of trial results, 6) main product field trials, 7) product revisions, 8) wide scale field trials/ feasibility test, 9) final product revision, 10) dissemination and implementation. The resulting product is a Biology learning module based on Multiple Intelligence as Biology teaching material with sub-material on the human digestive system for class VIII junior high school students. The module designed is an electronic module based on Multiple Intelligence where every human has 9 intelligences, namely: linguistic, logical, musical, spatial, kinesthetic, interpersonal, intrapersonal, naturalist, and existential. which is described based on the material that has been selected, the material chosen is the material on the Digestive System in Humans.